2016
DOI: 10.1155/2016/2183026
|View full text |Cite
|
Sign up to set email alerts
|

ROS‐Mediated NLRP3 Inflammasome Activation in Brain, Heart, Kidney, and Testis Ischemia/Reperfusion Injury

Abstract: Ischemia and reperfusion (I/R) causes a reduction in arterial blood supply to tissues, followed by the restoration of perfusion and consequent reoxygenation. The reestablishment of blood flow triggers further damage to the ischemic tissue through reactive oxygen species (ROS) accumulation, interference with cellular ion homeostasis, and inflammatory responses to cell death. In normal conditions, ROS mediate important beneficial responses. When their production is prolonged or elevated, harmful events are obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
253
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 419 publications
(278 citation statements)
references
References 104 publications
5
253
1
1
Order By: Relevance
“…45 In these organs, aPC likewise conveys cytoprotection after IRI, 15 suggesting that limiting inflammasome activation by aPC may be relevant not only in the heart and kidney (as shown here), but also in other organs. Of note, the 3K3A aPC variant has pronounced neuroprotective effects in animal models of cerebral IRI and is undergoing clinical trials in patients experiencing stroke (registered at www.clinicaltrials.gov as #NCT02222714).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…45 In these organs, aPC likewise conveys cytoprotection after IRI, 15 suggesting that limiting inflammasome activation by aPC may be relevant not only in the heart and kidney (as shown here), but also in other organs. Of note, the 3K3A aPC variant has pronounced neuroprotective effects in animal models of cerebral IRI and is undergoing clinical trials in patients experiencing stroke (registered at www.clinicaltrials.gov as #NCT02222714).…”
Section: Discussionmentioning
confidence: 57%
“…45 Intriguingly, mTORC1 regulates mitochondrial quality and ROS, 63 suggesting that inhibition of mTORC1 and mitochondrial ROS by aPC may be mechanistically linked. Because the regulation of mitochondrial ROS and mTORC1 is mutual, 64 additional studies are required to decipher the exact mechanism through which aPC regulates mTORC1 and mitochondrial ROS.…”
Section: 5152mentioning
confidence: 99%
“…We also examined whether E2 could regulate another upstream regulator of NLRP3, thioredoxin interacting protein (TXNIP). Following increased production of reactive oxygen species (such as what occurs after ischemic injury), TXNIP is released from its complex with thioredoxin (TRX) and can bind to the LRR region of NLRP3 and activate it [52, 53]. As shown in Supplementary Figure 3A, immunofluorescence staining revealed that TXNIP expression was increased in rat hippocampal CA1 region at 7 days after GCI and that this expression is robustly suppressed by E2 treatment.…”
Section: Resultsmentioning
confidence: 99%
“…One mechanism is driven at the transcriptional level by NF-κB, with the subsequent stimulation of Il1b gene expression. Another is induced at the post-transcriptional level and is associated with activation of the inflammasome, which converts the immature cytokine pro-IL-1β to the active form42. As ROS-mediated oxidative stress regulated the NF-κB pathway and inflammasome activation, Nrf2 deficiency increased IL-1β production through those two mechanisms by increasing ROS levels.…”
Section: Discussionmentioning
confidence: 99%